PENGUATAN MANAJEMEN PUSAT KEGIATAN BELAJAR MASYARAKAT DALAM MENINGKATKAN MUTU LAYANAN PENDIDIKAN NONFORMAL - Asep Saepudin; Ade Sadikin; Iip Saripah (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2016)
The purposes of this research are (a) to describe service conceptual model of Community Learning Center (CLC), (b) to validate the service conceptual model of CLC, and (c) to analyze the implementation of the service conceptual model of CLC. The research employed qualitative approach and descriptive method. The data were collected by using document study, literature review, interview, and Focus Group Discussion as from April through September 2015. The subjects of the study included administrators, tutors, and CLC participants in Bandung Raya area. The research resulted in (a) the developed conceptual model consisting of rationalization, assumption, objectives, components, indicators, and procedure model; (b) the model validation used peer group and expert judgement techniques; and model implementation described in instructional activities in CLC. Instructional steps as the model components are planning process, organizing, implementation, and evaluation in instruction. The conclusion of the developed model indicates effective results with the indicators: (a) the active participation and respond of the community for instructional activities and (b) the learning achievement of the community shows the improvement in knowledge, attitude, and skills.